Advokasi Regulasi Kepegawaian bagi Perangkat Desa Tanjung Mudo - Harmaini, Harmaini; Dahri, Muhtar; Chandra, Febrian; Arqon, Mohammad; Satria, Deni; Gusriyani, Nessie (PT. Meja Ilmiah Publikasi, 2025)
Professional village governance demands a comprehensive understanding from village officials of the regulations that govern their duties and functions. However, the reality on the ground shows a significant knowledge gap. This community service program aims to enhance the legal literacy and capacity of the officials of Tanjung Mudo Village, Jangkat Timur District, through advocacy on personnel regulations. The program was conducted on March 3-4, 2025, using a participatory method that combined interactive lectures, case studies, and Focus Group Discussions (FGDs). To measure the program's impact, pre-test and post-test instruments were utilized. The initial assessment results showed an average participant score of only 48 out of 100, indicating a low level of understanding regarding their rights, obligations, and personnel procedures. Following the advocacy program, there was a very significant increase in understanding, with the average post-test score jumping to 85 out of 100. This improvement proves that the applied advocacy method was effective in bridging the knowledge gap, thereby empowering village officials to work more professionally, accountably, and in accordance with the prevailing legal framework.